Interaction of Tillage Systems and Plant Spacing in Enhancing the Growth and Productivity of Lowland Rice (Oryza Sativa L) - Sulardi, Sulardi; Muhammad Sidik Tarigan; Ocdy Amelia (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the effects of soil tillage systems and planting spacing, along with their interaction, on the growth performance and productivity of lowland rice (Oryza sativa L.) variety IR64. The experiment was conducted in paddy fields using a factorial randomized block design (RBD) comprising two factors. The first factor, the soil tillage system, included three treatments: plowing (P1), tractor tillage (P2), and hoeing (P3). The second factor, planting spacing, consisted of three levels: 30×20 cm (J1), 30×30 cm (J2), and 30×40 cm (J3). Growth and yield parameters measured were plant height, number of tillers, leaf area, grain weight per clump, grain weight per plot, and estimated yield per hectare. The results revealed that the interaction between soil tillage systems and planting spacing significantly influenced the number of tillers, grain weight per clump, grain weight per plot, and grain yield per hectare, but had no significant effect on plant height and leaf area. The highest yield was achieved under the P2J2 combination (tractor tillage with 30×30 cm spacing), producing 600 g per 1 m² plot, equivalent to approximately 6 tons per hectare. These findings indicate that the combination of tractor tillage and moderate spacing enhances growth efficiency and yield potential in lowland rice (IR64 variety).